Bruton's tyrosine kinase potentiates ALK signaling and serves as a potential therapeutic target of neuroblastoma. Issue 47 (22nd November 2018) - Li, Tianfeng; Deng, Yi; Shi, Yu; Tian, Ruijun; Chen, Yonglong; Zou, Lin; Kazi, Julhash; Rönnstrand, Lars; Feng, Bo; Chan, Sun; Chan, Wai; Sun, Jianmin; et al.
Abstract Aberrant activation of anaplastic lymphoma kinase (ALK) can cause sporadic and familial neuroblastoma. Using a proteomics approach, we identified Bruton's tyrosine kinase (BTK) as a novel ALK interaction partner, and the physical interaction was confirmed by co-immunoprecipitation. BTK is expressed in neuroblastoma cell lines and tumor tissues. Its high expression correlates with poor relapse-free survival probability of neuroblastoma patients. Mechanistically, we demonstrated that BTK potentiates ALK-mediated signaling in neuroblastoma, and increases ALK stability by reducing ALK ubiquitination. Both ALKWT and ALKF1174L can induce BTK phosphorylation and higher capacity of ALKF1174L is observed. Furthermore, the BTK inhibitor ibrutinib can effectively inhibit the growth of neuroblastoma xenograft in nude mice, and the combination of ibrutinib and the ALK inhibitor crizotinib further enhances the inhibition. Our study provides strong rationale for clinical trial of ALK-positive neuroblastoma using ibrutinib or the combination of ibrutinib and ALK inhibitors.